A Structural Perspective on Faith and Values in Hamka’s Literary Body of Work - Stark, Alexander; Huszka, Balazs (LingPoet: Journal of Linguistics and Literary Research, 2024)
Da’wah, derived from Arabic, refers to the act of extending an invitation. Consequently, it encompasses the notion of persuading individuals to embrace the Islamic faith. Da’wah also seeks to encourage Muslims to adhere steadfastly to religious tenets. This invitation can be conducted using a multitude of methods. In this essay, the researchers contend that novels can serve as a potent means of da’wah. As an example, the works of Indonesian author Hamka were examined. The study of Hamka’s writings in relation to da’wah was conducted through the application of a structuralist and semiotic approach. We have found that these novels have a substantial readership and that they aim to conceptualise the world’s sufferings by creating binary pairs of oppositions. Within numerous narratives, the juxtaposition of opposing elements often reaches its climax in the concept of mortality, thus accentuating the true significance of existence. The readers will comprehend that their earthly existence is nearing its conclusion. Additionally, it was found that Hamka utilised a nuanced approach to imparting Islamic ideas: The primary figures in his literary works often provide guidance or communicate religious knowledge.